Knowledge management as a mediator of the impact of corporate social responsibility on sustainable development: Empirical evidence from a low-income country - Al-Fakih, Ebrahim Mohammed Mohammed; Almarani, Abdulrazaq Mohammed Qaid (International Journal of Innovative Research and Scientific Studies, 2025)
In developing countries, organizations face increasing pressure to incorporate Corporate Social Responsibility (CSR) into their strategic operations to promote Sustainable Development (SD). This study explores the role of Knowledge Management (KM) as a mediator between CSR and SD within Hayel Saeed Ana’am Group (HAS) in Yemen. It focuses on understanding how CSR activities influence KM practices and, consequently, how these practices facilitate the achievement of sustainability objectives. A quantitative research design with an explanatory focus was employed, utilizing a cross-sectional survey. Data were collected from 191 employees of HAS using a structured questionnaire. The collected data were analyzed through SPSS and SmartPLS to examine the relationships among CSR, KM, and SD and to evaluate the mediating effect of KM. The analysis reveals that CSR has a positive effect on both KM practices and SD outcomes. Moreover, KM plays a crucial mediating role, enhancing the impact of CSR initiatives on sustainable development. Within CSR dimensions, ethical responsibility emerged as the most influential, while environmental concerns were the most significant component of SD. Strong associations were found among all variables, supporting the validity of the proposed model. The findings suggest that integrating CSR into organizational strategies can effectively strengthen knowledge management processes, which in turn contribute to sustainable development. This study provides valuable empirical evidence from a low-Income country context, highlighting how robust KM practices can magnify the positive outcomes of CSR initiatives and support long-term sustainability.